Balancing fishery and conservation: a case study of the barrel jellyfish Rhizostoma octopus in South Wales. (20th September 2016) - Elliott, Anna; Hobson, Victoria; Tang, Kam W.
Abstract : In Wales, the barrel jellyfish Rhizostoma octopus is commercially harvested to produce high-value medical grade collagen. Although the fishery is presently not regulated, there are concerns how it may affect the leatherback turtle ( Dermochelys coriacea ), which preys on R. octopus in local waters. We combined monitoring data and morphometric and weight measurements in models to estimate the potential impact of R. octopus fishery on foraging turtles. We found a significant quadratic relationship between bell diameter and wet weight of R. octopus, with bell diameter explaining 88% of the variability in wet weight. R. octopus biomass in the Carmarthen Bay varied inter-annually between 38.9 and 594.2 tonnes y −1 . The amount of R. octopus needed to satisfy a leatherback turtle's daily energetic requirements was estimated at 85.1–319.1 kg. Using leatherback turtle sighting data, our models show that during a jellyfish 'low year", the R. octopus population could be completely depleted by an average of two foraging turtles along with the current level of commercial harvesting (4.3 tonnes). During a jellyfish "high year", the current level of commercial harvesting is predicted to have relatively little impact on food supply for even the maximum number of foraging leatherback turtle reported in the area. However, uncertainties related to the jellyfish's life cycle in the local waters need to be resolved for proper management of this emerging fishery.